Global talent management - Collings, David G.; Scullion, Hugh; Caligiuri, Paula (Routledge, 2019)
The second edition of Global Talent Management (GTM) offers a state of the art overview of the key areas of talent management in theory and practice. Drawing on contributions from the leading global contributors to talent management research, the book is structured around three key sections. Section one provides a contextual overview of talent management. The second section explores in depth some of the core areas of GTM practice which includes the meaning of talent in the global context, internal talent identification, developing leadership talent, employee turnover, employer branding and the role of the corporate HR function in GTM. The final section considers three key contemporary issues in GTM, namely, data analytics in GTM, managing virtual talent and managing globally diverse talent. The chapters in the volume provide advanced undergraduate or postgraduate students with an interest in global talent management with a cutting-edge overview of the key topics in the field. It is also an invaluable resource for the reflective practitioner looking for an overview of key research in this important area of practice
Description based on print version record
Keywords: International business enterprises / Personnel management; International business enterprises / Employees